LIMITATIONS OF POSITIVE LEGAL JURISPRUDENCE AND THE ROLE OF INDIAN SPIRITUALITY: SOME PRIMARY REFLECTIONS - Upadhyay, Santosh K; Acharya, Ashutosh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Except introduction, the paper has been divided into four parts. Part I gives the brief introduction of positive legal jurisprudence and highlights its basic problems. Part II elaborates upon the core values of the Indian Spiritualism and highlights the philosophical base of the Indian spiritualism from Upanishads. Part III discusses the application of Indian spiritual values into the Indian Constitution and also highlights the problems of non-invocation of spiritual vocabulary and categories into legal discussions and debates. Part IV ends the study with conclusion.